Anti-soiling coating performance assessment on the reduction of soiling effect in second-surface solar mirror. (December 2019) - Lopes, Daniel; Conceição, Ricardo; Silva, Hugo Gonçalves; Aranzabe, Estíbaliz; Pérez, Gema; Collares-Pereira, Manuel
Highlights: Soiling index calculated through data processing obtained from a Tracking Cleanliness Sensor. Particle deposition and soiling rates studied during different different periods of the year. Scanning Electron Microscopy and Energy Dispersive Spectroscopy analysis. Mirror performance and Cost-analysis for an Andasol-I type plant. Abstract: Soiling represents a major problem for CSP plants, since the accumulation of particles onto the reflective surface cause absorption and scattering of solar irradiance, leading to a significant decrease in the mirrors' reflectance. Such problem can be amplified, particularly in CSP plants that are installed in semi-arid or arid regions which possess a high direct normal irradiance availability, prone to higher particle deposition due to sand storms, red rain events and, in general, higher atmospheric particle concentration. As means to reduce the amount of dust adhering to the mirrors, anti-soiling coatings are being developed to reduce particle deposition, minimizing maintenance costs due to cleaning processes, leading to an enhancement of energy production. In this paper, a Tracking Cleanliness Sensor was used to compare the Soiling Index between a set of coated and uncoated mirrors, which were left outdoors to naturally accumulate soiling in two different positions, horizontal and tilted 45°. The anti-soiling coating was developed by a partnership between RIOGLASS and IK4-TEKNIKER. Moreover, a simple economical model is proposed here for different possible scenarios regarding the coating used.